INTEGRATED QUANTITATIVE ASSESSMENT OF CHANGES IN NEURO-ENDOCRINE-IMMUNE COMPLEX AND METABOLISM IN RATS EXPOSED TO ACUTE COLD-IMMOBILIZATION STRESS - Sydoruk, Sydoruk O; Zukow, Walery; Yanchij, Roman I (Journal of Education, Health and Sport, 2016)
Sydoruk Nadiya O, Zukow Walery, Yanchij Roman I. INTEGRATED QUANTITATIVE ASSESSMENT OF CHANGES IN NEURO-ENDOCRINE-IMMUNE COMPLEX AND METABOLISM IN RATS EXPOSED TO ACUTE COLD-IMMOBILIZATION STRESS. Journal of Education, Health and Sport. 2016;6(9):724-735. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159218 http://ojs.ukw.edu.pl/index.php/johs/article/view/3915 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. INTEGRATED QUANTITATIVE ASSESSMENT OF CHANGES IN NEURO-ENDOCRINE-IMMUNE COMPLEX AND METABOLISM IN RATS EXPOSED TO ACUTE COLD-IMMOBILIZATION STRESS Nadiya O Sydoruk1, Walery Zukow2, Roman I Yanchij3 1JSC “Dnipro-Beskyd”, Truskavets’, Ukraine dnipro-b@bk.ru 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl 3Department of Immunophysiology OO Bogomoletz Institute of Physiology NAS, Kyiv, Ukraine tas@biph.kiev.ua Abstracts Background. It is known that the reaction of the neuroendocrine-immune complex to acute and chronic stress are different. It is also known about sex differences in stress reactions. Previously we have been carry out integrated quantitative estimation of neuroendocrine and immune responses to chronic restraint stress at male rats. The purpose of this study - to carry out integrated quantitative estimation of neuroendocrine, immune and metabolic responses to acute stress at male and female rats. Material and research methods. The experiment is at 58 (28 male and 30 female) white rats Wistar line weighing 170-280 g (Mean=220 g; SD=28 g). The day after acute (water immersion restraint) stress determined HRV, endocrine, immune and metabolic parameters as well as gastric mucosa injuries and comparing them with parameters of intact animals. Results. Acute cold-immobilization stress caused moderate injuries the stomach mucosa as erosions and ulcers. Among the metabolic parameters revealed increased activity Acid Phosphatase, Asparagine and Alanine Aminotranspherase as well as Creatinephosphokinase. It was also found to reduce plasma Testosterone as well as serum Potassium and Phosphate probably due to increased Parathyrine and Mineralocorticoid activity and Sympathotonic shift of sympatho-vagal balance. Integrated quantitative measure manifestations of Acute Stress as mean of modules of Z-Scores makes for 10 metabolic parameters 0,75±0,10 σ and for 8 neuro-endocrine parameters 0,40±0,07 σ. Among immune parameters some proved resistant to acute stress factors, while 10 significant suppressed and 12 activated. Integrated quantitative measure poststressory changes makes 0,73±0,08 σ. Found significant differences integrated status intact males and females, whereas after stress differences are insignificant. Conclusion. The approach to integrated quantitative assessment of neuroendocrine-immune complex and metabolism may be useful for testing the effectiveness streslimiting means. Keywords: acute stress, HRV, hormones, immunity, metabolism, entropy, male and female rats.